Digital poverty as a barrier to access. (1st July 2022) - Butcher, John; Curry, George
Over the last 18 months, media coverage has revealed a concern that the increasing proliferation of digital learning at all universities (amplified by COVID-19 lockdowns) has compounded access and participation barriers for students impoverished by socio-economic challenges. This reflects the importance of digital capital as an aspect of learner disadvantage (Park, 2017) and increased understanding of intersectional disadvantage (Nichols and Stahl, 2019), through which digital disadvantage may add to pre-existing inequalities. The Quality Assurance Agency (2020) report how institutional action against digital poverty correlates with greater student satisfaction and higher levels of attainment. This article synthesises data from the authors' scholarship into digital barriers facing adult students returning to education. Challenges in relation to disposable income often compound challenges intersecting with other aspects of disadvantage (Butcher and Rose-Adams, 2015), and a lack of confidence and inadequate digital readiness amongst learners from disadvantaged backgrounds seeking an Access entry route has been identified (Curry and Butcher, 2020; Fowle and Butcher, 2019; Butcher and Fowle, 2018). Recommendations are made to promote greater inclusion amongst students from poor socio-economic backgrounds and to support the progression of a more diverse (and representative) adult learner cohort.